Famers' access to credit: Does collateral matter or cash flow matter? Evidence from Sindh, Pakistan - Abbas Ali Chandio; Yuansheng Jiang; Feng Wei; Abdul Rehman; Dan Liu (Cogent Economics & Finance, 2017)
Credit is highly demanded in different parts of the world, mainly for capital requirement to improve land, purchase of main agricultural inputs including fertilizers, seeds, pesticides, and purchase of farm machinery. The purpose of this study was to examine the farmers' access to credit: does collateral matter or cash flow matter?-evidence from Sindh province of Pakistan. The random sampling technique was used to collected data from 300 rural households through a face-to-face interview. To find the important factors affecting access to credit in Sindh province of Pakistan, we performed descriptive statistics and probit regression model. The results of probit regression model showed that gender, household size, educational level, farming experience, farm size, income, and availability of collateral have positive effect on farmers' access to credit, while age has a negative and statistically insignificant effect on the farmers' access to credit. Therefore, this study recommended that institutional sources of credit (such as the ZTBL and other Commercial Banks) should improve their loaning schemes to better suit the diversified needs of small farmers.
Keywords: 330; financial sources; credit access; probit model; Pakistan